A Cross-Layer Integration Framework for the Development of a Platform Business Model, Applications and Services - Strahonja, Vjeran; Oreški, Dijana (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Digital platforms have transformed contemporary economic structures by enabling multi-sided interactions, network effects, and ecosystem-based value creation. However, existing research frequently treats business models, technical architectures and service design as separate domains, resulting in conceptual fragmentation and practical misalignment. This paper proposes a cross-layer integration framework for the development of Digital Platform Business Models (DPBMs), platform applications, and platform services. The framework integrates lifecycle perspectives and construct mapping across business, service, and application layers. It introduces a bidirectional development logic that enables both top-down (business-driven) and bottom-up (technology-driven) innovation. By formalizing the transformation of Business Model Canvas (BMC) constructs into service design artifacts and Unified Modeling Language (UML) models, the framework enhances traceability, consistency, and alignment across layers. The study contributes to digital platform research by offering a structured methodological foundation for cross-layer integration and identifying future directions for tool-supported model transformation.